EFFECT OF LEAVES DEFOLIATION AND DATE OFDEFOLIATION ON GROWTH OF SUNFLOWER PLANT(Helianthus annuus L.) IN GYPSYFEROUS SOIL. - AL-Jobori, Kamil; Dirach, Firas (Iraqi Journal of Science, 2024)
The objective of the work was to study the effect of several leaves defoliation : non defoliation (control D1, defoliation of lower 25%D2, upper 25%D3, lower 50% D4, upper50% D5 of plant leaves, defoliation of 25D6, 40D7, and 50%D8 of plant leaves along the stem, and defoliation of all plant leaves. That took place at two stages of plant growth: vegetative growth to head (R1), and the period from heads opening to flowering (R4-R5), on growth of sunflower plant var.Euroflor in gypsyferous soil. The experiment was designed according to RCBD with three replications. Agricultural practices were made according to recommendations.Results indicated that defoliation of the lower 50% of plant leaves reduced leaf content of chl. a and total chl. by 58.7 and 40.4%, respectively as a mean of seasons. Defoliation of all plant leaves reduced stem length and its diameter by 27 and 47.6%, respectively as a mean of seasons.Non defoliation was superior in the dry weight of root and plant by 142 and 69.6%, respectively compared with defoliation of all plant leaves.When defoliation of all plant leaves, leaf area index,leaf area duration and relative growth rate were reduced by 98.7,7723 and 55.8,respectively. While crop growth rate increased by 120% after (72-86) days from planting as a mean of seasons.Defoliation of the leaves during (R4-R5) caused reduction in the content of chl. a,b and total chl. by 19.8, 10.2 and 12%,respectively.On the other hand, defoliation of the leaves during (R1) caused reduction in stem length and its diameter by 5.3 and 6.9%, respectively, and leaf area duration by 15.5% after (72-86) day from planting as a mean of seasons. We found significant interaction between defoliation and stages of plant growth in most studied characters.In conclusion, defoliation the lower 25% of plant leaves caused negative effect on root growth ,defoliation of lower 25% or 25 and 40% along the stem caused small effect on plant growth , whereas defoliation the lower and upper 50% of plant leaves have the highest effect on sunflower growth.